The Influence of the Regional Financial Accounting System and the Motivation of Public Services on the Performance of Local Governments - Haliah Haliah; Andi Kusumawati; Nurfaiqah Yunus (International Journal Labs, 2023)
This study aims to examine and analyze the effect of the financial accounting system and public services motivation on the local governments performance. This study uses primary data through survey methods by distributing questionnaires to 40 SKPD within the scope of the Makassar city government. The entire population of this study is a research sample. The data collected was then analyzed using multiple linear regression analysis. The results of this study indicate that there was a positive and significant effect of financial accounting system and public services motivation on the local governments performance. The findings of this study indicate that the better the financial accounting system is applied and the higher the public services motivation that are owned in every employee of the public sector, it will improve the performance of local governments.